The development of English pronunciation ability by using Phonics instruction for grade 6 students - Poonaklom, Suratsawadee; Phorntaweekul, Satjatham (Journal for Developing the Social and Community, 2023)
The purpose of this research is to develop English pronunciation ability. By using using Phonics instruction for grade 6 students with a passing score of 70 percent or more, the target group used in this research were Prathomsuksa 6 students at Khambongpittayakom School. Huai Phueng District, Kalasin Province, second semester of the academic year 2021, consisted of 10 students. The research instruments were 1) 7 learning management plans 2) measurement English pronunciation ability form 3) student learning behavior observation form. 4) Student interview form.The data were analyzed by finding percentages, averages, and summarizing the results in an essay. The findings: 1. The development of English pronunciation ability. By using Phonics instruction for grade 6, the researcher used an action research model. It was found that the students had scores on the English pronunciation ability measure higher than the specified criteria. That is, the students had The English pronunciation ability score on measurement passed the criteria of 70 percent or more, there were 10 people, representing 100 percent.